2012
DOI: 10.1155/2012/432176
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Conduction Delay in Fetuses Exposed to Anti-SSA/Ro and Anti-SSB/La Antibodies: A Magnetocardiography Study

Abstract: Background. The presence of anti-SSA/Ro and anti-SSB/La antibodies during pregnancy is associated with fetal congenital heart block (CHB), which is primarily diagnosed through fetal echocardiography. Conclusive information about the complete electrophysiology of the fetal cardiac conducting system is still lacking. In addition to echocardiography, fetal magnetocardiography (fMCG) can be used. fMCG is the magnetic analogue of the fetal electrocardiogram (ECG). Patients and Methods. Forty-eight pregnant women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Other diagnostic tests (electrocardiogram plus Holter monitor, magnetocardiography, gated-pulsed Doppler technique, velocity-based fetal kinetocardiogram) might detect subtle signs of the development of CHB, but their use is not standard practice. 9396 Serial echocardiograms and obstetric sonograms should be performed weekly from 16 weeks of gestation onwards, although the frequency might be reduced in the absence of CHB after week 26, as we found that <20% of cases are diagnosed after week 30 of gestation. Serial echocardiograms should also evaluate EFE, which might be subclinical, like type I CHB, but with a worse prognosis.…”
Section: Management Recommendationsmentioning
confidence: 76%
“…Other diagnostic tests (electrocardiogram plus Holter monitor, magnetocardiography, gated-pulsed Doppler technique, velocity-based fetal kinetocardiogram) might detect subtle signs of the development of CHB, but their use is not standard practice. 9396 Serial echocardiograms and obstetric sonograms should be performed weekly from 16 weeks of gestation onwards, although the frequency might be reduced in the absence of CHB after week 26, as we found that <20% of cases are diagnosed after week 30 of gestation. Serial echocardiograms should also evaluate EFE, which might be subclinical, like type I CHB, but with a worse prognosis.…”
Section: Management Recommendationsmentioning
confidence: 76%
“…Whilst CHB is the most widely studied and recognised aspect of fetal exposure to anti‐Ro antibodies, there are numerous reports of complications beyond those illustrated in this report. These include sinus bradycardia 6 , first degree AV block 1 , 3 , second degree AV block 2 , atrial flutter 2 , tricuspid valve chordal rupture with severe tricuspid regurgitation 5 and dilated cardiomyopathy 4 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…It is urgently necessary to define the susceptible populations, from both maternal and fetal aspects. [ 2 15 26 27 28 29 30 31 32 33 34 35 36 37 ] The efficacy of current approaches for preventing the CHB progression in affected fetus and recurrence in subsequent pregnancy as well as other autoimmune-mediated damages is still controversial. The parameters to weigh out the risk and benefit remain to be determined.…”
Section: Urrent D Ilemma In Cmentioning
confidence: 99%
“…While most of fetal CHB cases can be reliably diagnosed through fUCG, it fails to provide conclusive information regarding electrophysiology of the fetal cardiac conducting system. fMCG is the magnetic analog of the fetal electrocardiogram (fECG),[ 32 ] and fetal cardiac time intervals could be extracted from the fMCG recordings by predefined procedures. In addition, fMCG results may also be utilized to monitor disease progression.…”
Section: Iagnosis and H Eart mentioning
confidence: 99%
See 1 more Smart Citation